APLIKASI PENENTUAN LOKASI GUDANG DISTRIBUSI AIR MINERAL MENGGUNAKAN GRAVITY LOCATION MODEL - Adriantantri, Emmalia; Pranoto, Yosep Agus; Priyasmanu, Thomas (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
Mineral Water Depot is a company engaged in distribution of mineral water. Constraints experienced so far the distribution process is less optimal because of the large number of customers, as well as the spread of the locations. The purpose of this research is to build Gravity Location Model application which could be used to determine the most appropriate location for the new warehouse, so that the distribution process becomes more optimal. With the use of this application process of lengthy calculations and the amount of retails can be done more quickly, easily and has a high accuracy. The result of this research is an application called Gravity Location Model to determine the location of the new warehouse, where calculations can be done quickly, easily with a better accuracy compared to manual calculation. Key word : optimization of Distribution, Gravity Location Model